Second language teacher education - Richards, Jack C. (Cambridge Univ. Press, 1990)
It offers valuable ideas on the observation and supervision of classrooms, on self-evaluation by teachers, and on teaching itself. Its emphasis reflects the shift in orientation from teacher training to teacher education, in which teachers are involved in developing their own theories of teaching, understanding the nature of teacher decision making, and developing strategies for critical self-evaluation